Analisis Pedagogis Penggunaan ChatGPT oleh Mahasiswa UIN SU dalam Penyusunan Tugas Akhir - M. Abrar Haq Salam; Hamidah Darma (Journal of Innovative and Creativity, 2026)
This study, titled “Pedagogical Analysis of ChatGPT Use by UIN SU Students in Final Project Preparation,” explores how university students integrate ChatGPT into their academic writing processes. Using a qualitative case study approach, the research investigates the experiences of final-year students at UIN Sumatera Utara who actively employ ChatGPT as a digital learning tool. The findings reveal that ChatGPT functions as a form of digital scaffolding that assists students in overcoming initial writing barriers, conceptualizing research frameworks, and improving academic language. From a pedagogical perspective, the use of ChatGPT aligns with Piaget’s constructivist theory and Vygotsky’s scaffolding concept, emphasizing active knowledge construction supported by temporary cognitive assistance. However, the study also highlights the ethical dimension of AI use in academia, stressing the importance of honesty, responsibility, and academic integrity. When used reflectively and critically, ChatGPT can enhance students’ learning autonomy and critical thinking without diminishing originality. The research concludes that responsible integration of AI in higher education requires balanced pedagogical guidance that fosters both technological literacy and ethical awareness.